Prevention and rehabilitation of common injuries in cyclists (Research, Society and Development, 2025)
Introduction: With the increasing practice of cycling, both as a sport and as a means of transportation, a higher prevalence of activity-related injuries has been observed. Objective: This article aims to review the literature on the role of physical therapy in preventing and rehabilitating common injuries among cyclists. Methods: A narrative literature review was conducted by searching the PubMed, SciELO, and PEDro databases for studies published between 2000 and 2024. Results: Physical therapy interventions, including bicycle posture adjustments, muscle strengthening exercises, and rehabilitation strategies, proved effective in preventing and rehabilitating injuries, significantly contributing to health promotion and improved cycling performance. Conclusion: It is concluded that physical therapy offers personalized and evidence-based approaches, reducing the incidence of injuries. However, further studies are needed to enhance preventive and rehabilitation practices specific to cyclists.